Joseph Smith, Polygamy, and the Levirate Widow - Brown, Samuel Morris (Dialogue, 2016)
The article presents the author's views on Mormon polygamy which has been abandoned by the church in the 1900s. Mormon leader Joseph Smith and his colleagues reportedly promoted polygamy as it is in line with the behaviors and doctrines of Bible patriarchs and addresses cultural problems. Also discussed are Biblical verses promoting polygamy, the importance of families in the society, the Sadducean thought experiment, and the conceptual structures of Mormon polygamy.